Docking fundamentals for simulation in nanoscience - Martins, Mirkos Ortiz; da Silva, Ivana Zanella; Fagan, Solange Binotto; dos Santos, André Flores (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
This work reviews the literature on the molecular docking process, presenting the simulation methodology, the construction parameters and how the results are interpreted. In this context, a study of molecular docking is carried out using the binding protein of the COVID-19 virus with the human cell, called spike, and an antiviral molecule called heparin. As a result, the parameters reached, distances, energies and three-dimensional positioning of the ligand-receptor system are shown. This type of work is currently done in the area of discovering new drugs, or drugs discovered with the aid of the computer. As a final discussion, it concludes the importance of computational knowledge as a way to support various chemical, physical and biological activities in the multidisciplinary field of nanoscience and nanotechnology.